Oxidation behaviour and kinetic properties of shape memory CuAlxNi4 (x=13.0 and 13.5) alloys - Zengin, R; Ozgen, S; Ceylan, M (Elsevier Science Bv, 2004)
Although the copper-based shape memory alloys (SMA) have some important problems such as controlling of the kinetic properties in the shape memory ability, they have relatively more advantages when compared to nitinol, such as lower price and simpler production technology. In order to determine the kinetic properties and oxidation rates of shape memory CuAlxNi4 (x = 13 and 13.5) alloys with polycrystalline forms, the alloys have been homogenized in beta-phase field at 930degreesC for 30 min and immediately quenched in iced-brine water at -3degreesC. The transformation temperatures in a period of three thermal cycles which include heating and cooling processes have been determined through Shimadzu DSC-50 differential scanning calorimeter. Activation energies of forward and reverse martensitic transformations have been calculated by using the Kissenger method. Thermogravimetric analysis with Shimadzu TGA-50 have been carried out for the determination of mass changes of alloys during heating and cooling cycles with two temperature rates selected as 10 and 30degreesC/min up to 900degreesC. It has been shown that increasing aluminium content reduces the oxidation rates of the alloys. It has also been established that CuAlNi shape memory alloys have a good stabilization in martensitic phase. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: shape memory effect; transformation temperatures; activation energy; oxidation behaviour